KELUARGA KRISTEN SEBAGAI KELUARGA ALLAH - Damayanti Nababan (Jurnal Christian Humaniora, 2019)
As we know, in Genesis 2: 18, God said: "It is not good if humans are alone. I will make the helper for him who is commensurate with him. "From these scriptures we can know that the formation of a Christian family is God's initiative it self. So a Christian family is a life alliance between father, mother, and children who have believed and accepted Jesus Christ as Lord and Savior personally and imitated his life and teachings in daily life. This understanding is built on Christian understanding it self. Christian means to be a follower of Christ who emulates the life and teachings  of Christ. In the process, the Christian family must be rooted, grow, and bear fruit in Christ. Christian families must be able to be a blessing to others. Applying Christian values in everyday life. BAHASA INDONESIA ABSTRACT: Sebagaimana yang kita ketahui, dalam Kejadian 2 : 18 , Tuhan Allah berfirman : “Tidak baik kalau manusia itu seorang diri saja. Aku akan menjadikan penolong baginya yang sepadan dengan dia” Dari nats tersebut dapat kita ketahui bahwa terbentuknya keluarga Kristen merupakan inisiatif Allah itu sendiri. Jadi keluarga Kristen merupakan persekutuan hidup antara ayah, ibu, dan anak - anak yang telah percaya dan menerima Yesus Kristus sebagai Tuhan dan Juruselamat secara pribadi serta meneladani hidup dan ajaran - ajaranNya dalam kehidupan sehari - hari. Pengertian ini dibangun dari pengertian Kristen itu sendiri. Kristen artinya menjadi pengikut Kristus yang meneladani hidup dan ajaran - ajaran Kristus. Dalam prosesnya, keluarga Kristen harus berakar, bertumbuh, dan berbuah dalam Kristus. Keluarga Kristen harus mampu menjadi berkat bagi orang lain. Menerapkan nilai - nilai Kristiani dalam kehidupan sehari - hari.Keywords: Christian Family, God's Family